Perceraian Akibat Orang Ketiga dalam Perspektif Hukum Positif dan Hukum Islam - Sukasna Sukasna; Siti Ngainnur Rohmah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
The phenomenon of family disunity that has been happening lately seems to have become a culture. This can be seen from the rise of adultery, divorce and marriage, then the increase in the number of street children seems to show negative symptoms in the community environment. The purpose of this study is to find out how divorce is due to a third person in a positive law perspective in the South Jakarta Religious Court and to find out how divorce is due to a third person in the Perspective of Islamic Law in the South Jakarta Religious Court. This research method is a qualitative research with a legal concept analysis approach. The results of the study show that: Divorce due to a third person in a positive legal perspective at the South Jakarta Religious Court in 2022 is regulated in Law Number 1 of 1974 concerning Marriage. Divorce in the view of Islam is not something that is prohibited but Allah hates the existence of a divorce. If forced, divorce is the last resort when all efforts to maintain the household have been made but to no avail.Key words: Divorce due to third party, South Jakarta Religious Court Abstrak Fenomena perpecahan keluarga yang banyak terjadi belakangan ini seolah menjadi suatu budaya. Ini dapat dilihat dari maraknya perselingkuhan, kawin cerai, kemudian ditambah meningkatnya jumlah anak jalanan seakan menunjukkan gejala-gejala negatif pada lingkungan masyarakat. Tujuan pada penelitian ini adalah untuk mengetahui bagaimana perceraian akibat orang ketiga dalam perspektif hukum positif di Pengadilan Agama Jakarta Selatan dan untuk mengetahui perceraian akibat orang ketiga dalam Perspektif Hukum Islam di Pengadilan Agama Jakarta Selatan. Metode penelitian ini adalah penelitian kualitatif dengan pendekatan analisis konsep hukum. Hasil penelitian menunjukan bahwa: Perceraian akibat orang ketiga dalam perspektif hukum positif di Pengadilan Agama Jakarta Selatan Tahun 2022 diatur dalam Undang-undang Nomor 1 Tahun 1974 Tentang Perkawinan. Perceraian dalam pandangan Islam bukan sesuatu yang dilarang namun Allah membenci adanya sebuah perceraian. Jika terpaksa, perceraian adalah jalan terakhir ketika semua upaya mempertahankan rumah tangga telah dilakukan namun tidak membuahkan hasil.Kata kunci: Perceraian Akibat Orang Ketiga Pengadilan Agama Jakarta Selatan